PARENTS’ ROLE TOWARDS IMPROVING THE PERFORMANCE OF THEIR CHILDREN IN SCHOOL WORK: A CASE STUDY OF BINDURA PRIMARY SCHOOLS - KASOWE, RITTAH (IJRDO- Journal of Educational Research, 2017)
The purpose of this present study was to investigate the role played by parents in improving the performance of their children in school work in Bindura primary schools in Zimbabwe using the quantitative research methodology. The population consisted of all heads, SDC/SDA members and teachers in the thirty schools in Bindura. Random sampling was used to arrive at a sample of ninety six (96) respondents made up of six (6) heads of schools, seventy two (72) teachers and eighteen (18) members of School Development Committees or Associations (SDCs/SDAs). The questionnaire and interview were used for data collection. The study revealed that there are many barriers to effective parental involvement in school activities such as lack of education by parents. The study recommends that heads of schools should always involve parents before making decisions that require the inputs from the parents. There should also be staff development workshops for teachers and parents where parental involvement in the education of their children would be the main topic.